Wealth in the Perspective of the Qur'an: An Exploration Through the Maudhui’s Exegesis Approach - Faradina, Gita Nurul; Makmun, Muhammad (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2024)
Humans cannot be separated from wealth. Even as Muslims, in performing acts of worship or transactions, wealth is needed, for instance, in performing Hajj. The reality is that many Muslims are unable to perform Hajj due to financial constraints. This situation is exacerbated by stereotypes from preachers, such as on Teuku's YouTube channel, where he stated that Allah hastens the rewards for non-believers in this world while Muslims will receive them in the hereafter. This can become a mental block for Muslims, causing them to resign to their circumstances and be reluctant to strive for stable financial goals. Additionally, there is a ḥadīṡ narrated by at-Tirmiżi where the Prophet prayed to live and die in a state of poverty because the poor will enter paradise earlier than the wealthy. However, upon closer examination, this ḥadīṡ is considered ḥadīṡ garib and cannot be used as a binding proof. It can be seen that being wealthy is not prohibited, as it can make many things easier for us. However, everyone's definition of wealth is different. To address this issue, the author employs a Maqasidi interpretation approach using descriptive analysis. The article finds that the orientation of wealth according to the Qur'an is not solely focused on material possessions but rather towards spiritual orientation (inner wealth). Abundance holds significant importance in fulfilling life's needs, both in worship (ibadah mahdlah) and transactions (muamalah). However, the article highlights that true wealth lies in richness of the heart, as financial wealth not used for the good of Allah's path may be in vain and provide no benefit in the afterlife. Therefore, a balance between worldly and hereafter aspects is needed in attaining wealth.